Pathological gamblers are more vulnerable to the illusion of control in a standard associative learning task - Orgaz, Cristina; Estevez, Ana; Matute, Helena (Frontiers in Psychology, 2013)
An illusion of control is said to occur when a person believes that he or she controls an outcome that is uncontrollable. Pathological gambling has often been related to an illusion of control, but the assessment of the illusion has generally used introspective methods in domain-specific (i.e., gambling) situations. The illusion of control of pathological gamblers, however, could be a more general problem, affecting other aspects of their daily life. Thus, we tested them using a standard associative learning task which is known to produce illusions of control in most people under certain conditions. The results showed that the illusion was significantly stronger in pathological gamblers than in a control undiagnosed sample. This suggests (a) that the experimental tasks used in basic associative learning research could be used to detect illusions of control in gamblers in a more indirect way, as compared to introspective and domain-specific questionnaires; and (b), that in addition to gambling-specific problems, pathological gamblers may have a higher-than-normal illusion of control in their daily life.